The Role of Mother Cares (MOCA) for Compliance Applications of Parents in Stimulating Growth and Development of Children Aged 24 to 36 Month in Working Area of Puskesmas Kabanjahe - Pinem, Srilina Br; Manurung, Herna Rinayanti; Damanik, Lisa (Proceeding - Sari Mutiara Indonesia International Conference on Health, 2018)
Therefore, the basic skill needed by the children needs to be stimulated by directed-teach in gross motor skills, fine motor skill, speech and language skills, and socialization and independence. Mother Care’s application (MOCA) in 24to 36 months of postnatal age can be used as the supportive tool used by the parent to help to detect growth and developmental impairments and also to stimulate children in that age. The standard procedure for the growth and developmental stimulation for the children in 24to36 month of postnatal age can be found in MOCA application of 24to36 month of postnatal age which is presented in an animated motion with the timely reminder. This research used queasy experiment model with pre-posttest with control group design, to assess the role of Mother Cares application (MOCA) toward parents compliance in stimulating growth and development of children 24to 36 months of postnatal age. This research was conducted at the Primary health care Kabanjahe from June to July 2017 with a total sample of 45 parents who have smartphone kind of cellular phone. The result of this research showed that age, education, and occupation of parents does not show a true difference with p-value more than 0,05. It is proven that MOCA application in stimulating growth and development of children 24to 36 months of postnatal age increase knowledge of parents in stimulating growth and development of children 24to36 month of postnatal age with p-value is 0,000 and it is proven to increase parents skill in stimulating growth and development of children 24to 36 months of postnatal age with p-value is 0,001. Parents compliance in stimulating children's development includes gross motoric skill, fine motoric skills, speech, language, socialize skill and independence showed a certain difference with a p-value less more 0,001. Based on this research we can conclude that Mother Cares Application (MOCA) toward parent’s compliance in stimulating growth and development of children 24to 36 months of postnatal age in the working area of the primary health care Kabanjahe, 2017 showed an increase of compliance 1.9 times higher than the control group